Determination of regulation characteristics of capacitor exciter with variable topology for self-excited induction generator - Vasylets, Sviatoslav; Vasylets, Kateryna; Ilchuk, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2025)
The object of the study is a capacitor exciter with variable topology, designed to operate as part of an autonomous induction generator. Insufficient efficiency of controlling the excitation level of an autonomous induction generator when changing the speed of the drive turbine and the load impedance has been established. This reduces the quality of the generator output voltage. The possibility of using an exciter circuit based on a mixed connection of capacitors has been analyzed. The influence significance of the groups number and the number of capacitors in each group on the range width and the adjustment step has been confirmed. In particular, increasing the values of the specified factors from 2 to 4 expands the adjustment range by 16 times, and the number of steps by 827 times. With the selected intervals of factors variation and a significance level of 0.05, the influence of the capacitors value changing step, compared to the base one, on the relative value of the exciter capacitance changing step is recognized as insignificant. The total capacitance of the exciter depends significantly nonlinearly on the number of the topological state. An increase in the total capacitance is accompanied by a raising in the intensity of its growth. This allows to minimize the step change in the total capacitance (with a probability of 0.88 – up to 0.003 % of the control range width). The resulting regression mathematical model can be used to optimize the exciter structure for an autonomous induction generator of a specific type. Increasing the number of control stages will enhance the accuracy of forming the capacitive excitation current of the generator and compensating the load current inductive component. The use of an exciter with a variable topology will increase the efficiency of voltage control of an autonomous induction generator when changing the speed of the drive turbine and the load impedance